Redox-responsive micellar nanoparticles from glycosaminoglycans for CD44 targeted drug delivery - Carvalho, A. M. (2018)
Cancer progression is associated with overexpression of various receptors at the cell surface. Among these, CD44 is known to recognize and bind specifically hyaluronan (HA) and interact with less affinity to other glycosaminoglycans (GAGs), such as chondroitin sulfate (CS). In this study, we describe a simple method to obtain micellar nanoparticles with a GAG shell (HA or CS) as potential drug delivery systems that target cancer cells overexpressing CD44. Alkanethiol was conjugated at the reducing end of the respective GAG using highly efficient oxime chemistry. The alkane moiety confers amphiphilic behavior to the obtained conjugates and triggers their self-assembly into micellar nanoparticles, while the thiol group adds redox-responsiveness to the system. The properties of the particles depend on the used GAG: HA amphiphiles form more dense, smaller assemblies that are redox sensitive. Both systems allow encapsulation of either hydrophobic or hydrophilic cargos with high efficiency. We demonstrate that the GAGs exposed on the surface of the nanoparticles are with preserved bioactivity and recognized by the cellular receptors: the particles were internalized via CD44 dependent pathways.